Latihan Pliometrik Depth Jump Terhadap Power Otot Tungkai Pada Peserta Ekstrakurikuler Bola Voli - Insanistyo, Bayu; Alamsyah, Yusuf; Nopiyanto, Yahya Eko; Prabowo, Andika (STAMINA, 2024)
This research aims to determine the effect of plyometric depth jump training on leg muscle power in volleyball extracurricular participants at SMP Negeri 20 Bengkulu City. This type of research is quantitative with the method used is the experimental method and the research design uses one group pre-test and post-test design. The sample from this research was the volleyball extracurricular participants at SMP Negeri 20 Bengkulu City with a total of 10 students. Data collection uses the vertical jump test. The research showed significant results in terms of influence from the average pretest result of 35.7 followed by treatment and then the average posttest result was 48.4. Data analysis in this research uses prerequisite tests, namely the Normality test, Homogeneity test, and influence test. The statistical requirements test meets the homogeneity requirements and the data is normally distributed based on statistical calculations, the results obtained from the t-count data are 26.12 > t-table 1.83. Based on the research results, it was concluded that there was a significant effect of plyometric depth jump training on leg muscle power in volleyball extracurricular participants at SMP Negeri 20 Bengkulu City after being given the treatment 16 times.